Practical handbook of school psychology : effective practices for the 21st century - Gimpel Peacock, Gretchen (New York ; London : Guilford Press, 2010)
Part I: The School Psychologist as a Problem Solver: Establishing a Foundation and a Vision. Ervin, Peacock, Merrell, The School Psychologist as a Problem Solver in the 21st Century: Rationale and Role Definition. Hawkins, Barnett, Morrison, Musti-Rao, Choosing Targets for Assessment and Intervention: Improving Important Student Outcomes. Part II: Assessment and Analysis: Focus on Academic Outcomes. VanDerHeyden, Analysis of Universal Academic Data to Plan, Implement, and Evaluate Schoolwide Improvement. Floyd, Assessment of Cognitive Abilities and Cognitive Processes: Issues, Applications, and Fit within a Problem-solving Model: Focusing on Academic Achievement. Marcotte, Hintze, Assessment of Academic Skills in Reading within a Problem-solving Model. Burns, Klingbeil, Assessment of Academic Skills in Math within a Problem-solving Model. Gansle, Noell, Assessment of Academic Skills in Written Expression within a Problem-solving Model. Daly III, Hofstadter, Martinez, Andersen, Selecting Academic Interventions for Individual Students. Part III: Assessment and Analysis: Focus on Social Emotional and Behavioral Outcomes. McIntosh, Reinke, Herman, Schoolwide Analysis of Data for Social Behavior Problems: Assessing Outcomes, Selecting Targets for Intervention, and Identifying Need for Support. Martens, Ardoin, Assessing Disruptive Behavior within a Problem-solving Model. Miller, Assessing Internalizing Problems and Well-being. Jones, Wickstrom, Using Functional Assessment to Select Behavioral Interventions. Part IV: Implementing Prevention and Intervention Strategies. Stoiber, DeSmet, Guidelines for Evidence-based Practice in Selecting Interventions. Howell, Schumann, Proactive Strategies for Promoting Learning. Merrell, Levitt, Gueldner, Proactive Strategies for Promoting Social Competence and Resilience. Linan-Thompson, Vaughn, Evidence-based Reading Instruction: Developing and Implementing Reading Programs at the Core, Supplemental, and Intervention Levels. Chard, Ketterlin-Geller, Jungjohann, Baker, Evidence-based Math Instruction: Developing and Implementing Math Intervention Programs at the Core, Supplemental, and Intervention Levels. McCurdy, Schmitz, Albertson, Evidence-based Written Language Instruction: Teaching Written Language Skills at the Core. MacKay, Andreou, Ervin, Peer-mediated Intervention Strategies. Hoff, Sawka-Miller, Self-management Interventions. Gilbertson, Sonnek, Interventions for Homework Problems. Detrich, Higbee, Teaching Functional Life Skills to Children with Developmental Disabilities: Acquisition, Generalization, and Maintenance. Friman, Volz, Haugen, Parents and School Psychologists as Child Behavior Problem-solving Partners: Helpful Concepts and Applications. Shriver, Allen, Parent Training: Working with Families to Develop and Implement Interventions. Bushman, Peacock, Problem-solving Skills Training: Theory and Practice in the School Setting. Swearer, Givens, Frerichs, Cognitive-Behavioral Interventions for Depression and Anxiety. Kern, Benson, Clemens, Strategies for Working with Severe Challenging and Violent Behavior. DuPaul, Weyandt, Booster, Psychopharmacological Interventions. Part V: Evaluating Interventions. Daly III, Barnett, Kupzyk, Hofstadter, Barkley, Summarizing, Evaluating, and Drawing Inferences from Intervention Data. Noell, Empirical and Pragmatic Issues in Assessing and Supporting Intervention Implementation in Schools. Part VI: Building Systems to Support the Problem-solving Model. Sheridan, Magee, Blevins, Swanger-Gagne, Collaboration across Systems to Support Children and Families. Alsop, Dawson, Schaughency, The School Psychologist's Role in Assisting School Staff in Establishing Systems to Manage, Understand, and Use Data. Rhodes, Implementing the Problem-solving Model with Culturally and Linguistically Diverse Students. Tilly III, Niebling, Rahn-Blakeslee, Making Problem-solving School Psychology Work in Schools.
School psychologist as a problem solver in the 21st century: rationale and role definition / Ruth A. Ervin, Gretchen Gimpel Peacock, and Kenneth W. Merrell -- Choosing targets for assessment and intervention : improving important student outcomes / Renee O. Hawkins [and others] -- Analysis of universal academic data to plan, implement, and evaluate schoolwide improvement / Amanda M. VanDerHeyden -- Assessment of cognitive abilities and cognitive processes : issues, applications, and fit within a problem-solving model / Randy G. Floyd -- Assessment of academic skills in reading within a problem-solving model / Amanda M. Marcotte and John M. Hintze -- Assessment of academic skills in math within a problem-solving model / Matthew K. Burns and David A. Klingbeil -- Assessment of skills in written expression within a problem-solving model / Kristin A. Gansle and George H. Noell -- Selecting academic interventions for individual students / Edward J. Daly III [and others] -- Schoolwide analysis of data for social behavior problems : assessing outcomes, selecting targets for intervention, and identifying need for support / Kent McIntosh, Wendy M. Reinke, and Keith C. Herman -- Assessing disruptive behavior within a problem-solving model / Brian K. Martens and Scott P. Ardoin -- Assessing internalizing problems and well-being / David N. Miller -- Using functional assessment to select behavioral interventions / Kevin M. Jones and Katherine F. Wickstrom -- Guidelines for evidence-based practice in selecting interventions / Karen Callan Stoiber and Jennifer L. DeSmet -- Proactive strategies for promoting learning / Kenneth W. Howell and Joan Schumann -- Proactive strategies for promoting social competence and resilience / Kenneth W. Merrell, Verity H. Levitt, and Barbara A. Gueldner -- Evidence-based reading instruction : developing and implementing reading programs at the core, supplemental, and intervention levels / Sylvia Linan-Thompson and Sharon Vaughn -- Evidence-based math instruction : developing and implementing math programs at the core, supplemental, and intervention levels / David J. Chard [and others] -- Evidence-based written language instruction : developing and implementing written language programs at the core, supplemental, and intervention levels / Merilee McCurdy, Stephanie Schmitz, and Amanda Albertson -- Peer-mediated intervention strategies / Leslie MacKay, Theresa Andreou, and Ruth A. Ervin -- Self-management interventions / Kathryn E. Hoff and Kristin D. Sawka-Miller -- Interventions for homework problems / Donna Gilbertson and Rebecca Sonnek -- Teaching functional life skills to children with developmental disabilities : acquisition, generalization, and maintenance / Ronnie Detrich and Thomas S. Higbee -- Parents and school psychologists as child behavior problem-solving partners : helpful concepts and applications / Patrick C. Friman, Jennifer L. Volz, and Kimberly A. Haugen -- Parent training : working with families to develop and implement interventions / Mark D. Shriver and Keith D. Allen -- Problem-solving skills training : theory and practice in the school setting / Bryan Bushman and Gretchen Gimpel Peacock -- Cognitive-behavioral interventions for depression and anxiety / Susan M. Swearer, Jami E. Givens, and Lynae J. Frerichs -- Strategies for working with severe challenging and violent behavior / Lee Kern, Jaime L. Benson, and Nathan H. Clemens -- Psychopharmacological interventions / George J. DuPaul, Lisa L. Weyandt, and Genery D. Booster -- Summarizing, evaluating, and drawing inferences from intervention data / Edward J. Daly III [and others] -- Empirical and pragmatic issues in assessing and supporting intervention implementation in schools / George H. Noell -- Collaboration across systems to support children and families / Susan M. Sheridan [and others] -- School psychologist's role in assisting school staff in establishing systems t
Includes bibliographical references and indexes.
Keywords: School psychology -- United States; School psychology; United States; USA; USA; USA